Islamic Fundamentalism in the Contemporary Middle East as an alternative to secularism. Analisys of the Case of Iran ap to Muhammad Khatami's goverment. Part II - López Brenes, Manuel Enrique (2021)
The Part II of this essay analyses the profound transformations of the economy, the industry, the bank system, and in general de Iranian society, after the triumph of the Iranian Islamic Revolution back in 1979. This Part II also deals with the fact that Khumayni, since his arrival to power, proposed the political, economic and social possibility that religion would be an alternative to capitalism, to the dynasty in power, to secularism and to the Shah Muhammad Reza Pahlavi. Khumayni`s regime was also abusive, and came to be as repressive as the Shah’s. Iran’s extreme nationalization plans under Khumayni’s goverment experienced a systematic process of revisions, obviously after Khumayni’s death in 1989. These revisions and changes in politics, and the economy of the country led to an increasing opening to privatization, capitalism and globalization due to the more moderate governments that followed after Khumayni’s death in 1989, mainly those more moderate of Rafsanjani and Khatami, as this is explained in this Part II. The contrast between the two periods of the Islamic Republic is so evident that a Second Republic of Iran was founded and developed. This Part II also provides a number of tables and statistical data, which guides de reader to an easier understanding of the numerous transformations of Iran in the last decades of the 20th century and the first years of the 21th century.